The Effect Of Canva-Based Learning Materials On Pupils’ Creativity - Jumiati Siska; Mesterjon Mesterjon; Ema Pitriyanti (Journal of Educational Studies, 2024)
The growing use of visual design platforms in classrooms has intensified scholarly debate on whether digital learning media directly foster creativity or merely provide attractive instructional surfaces. This study examines the effect of Canva-based learning media on students’ creativity by integrating two competing theoretical perspectives: Cognitive Theory of Multimedia Learning, which emphasizes visual-verbal processing and reduced cognitive load, and the Componential Theory of Creativity, which highlights intrinsic motivation, domain-relevant skills, and creativity-relevant processes. A quasi-experimental pretest-posttest control group design was proposed involving 120 senior secondary students assigned to an experimental class using Canva-based instructional media and a control class using conventional slide-based media. Creativity was measured through a performance rubric covering fluency, flexibility, originality, and elaboration, while engagement and intrinsic motivation were assessed using validated Likert-scale instruments. Data were analyzed using descriptive statistics, reliability testing, independent samples t-test, ANCOVA, effect size estimation, and mediation analysis. Illustrative results show that students in the Canva-based group achieved higher posttest creativity scores than the control group after controlling for baseline ability, with the strongest gains observed in elaboration and originality. The discussion suggests that Canva supports creativity when its visual affordances are embedded in inquiry-oriented tasks, peer feedback, and teacher scaffolding. This study fills the void by positioning Canva not as a stand-alone technological solution but as a pedagogical design environment whose impact depends on cognitive, motivational, and social learning mechanisms. The findings offer implications for digital media integration, teacher training, and creativity-oriented curriculum design.